The determinants of users' behaviour on social media: the role of religion and personal values - Abu Bakar, Elistina; Draman, Nur Jannah; Zuhid Saidin, Aznan (Human Resource Management Academic Research Society, 2021)
The objective of this paper is to examine the role of religion and personal values as the determinants of users’ behaviour on social media. The role of religion refers to the level of religiosity and the perceptions towards Maqasid al-Shariah principles. Age factor regarding the behaviour was also explored. This study was an exploratory study which only involved one hundred and sixty Muslim users of social media in Kuala Terengganu who were chosen through random sampling. The Social Cognitive Theory was used to explain the users’ behaviour. The analysis shows that the level of religiosity, the perceptions towards Maqasid al-Shariah and personal values explain 33.6% variance in the behaviour of the respondents while using social media and the level of religiosity becomes the main determinant. This finding gives a significant implication to government, consumer movements and users so that the pillars of religion should be embedded in all education policies and programs to inculcate good behaviour among users of social media.